Laparoscopic Appendicectomy Using "Mian Waleed’s (MW) Ultragrasper - Waleed Anjum, Sayed Zamen Ali, Muhammad Imran, Mohsin Mumtaz, Muhammad Saad Ashraf, Hijab Siddique (Pakistan Journal of Medical & Health Sciences, 2022)
Introduction: The two Port Laparoscopic Appendectomy (TPLA) methods sits between the single port laparoscopic surgery and traditional three port trocar. Though TPLA, the appendix is ​​held with sutures, which creates a risk of perforation and trouble in exploration. Objective: The paper represents our experience with the usage of needle grasper in two Ports Laparoscopic Appendectomy to manipulate and suspend the appendix. Methods: 36 (11 women, 25 men) who endured TPLA were retrospectively analyzed in terms of duration of surgery, patient demographics, conventional laparoscopy or the need for laparotomy, complications, drain use and extent of hospital stay. The MW ultragrasper was placed just below the quadrant of abdomen at McBurney’s point without giving incision to manipulate and hang the appendix. Results: 26.80 ± 7.61 years was the mean age with 22.68 ± 3.88 kg / m2 mean body mass index (BMI). The ASA score was 1 and 2. In 34 patients, the operation was accomplished deprived of an extra trocar. 58.11 ± 3.29 mints were the mean operative time. No patient has any intraoperative complications. Drains were obligatory in three patients; They were all discharged after removing the drain. 31 subjects were discharged on the first day after surgery; 3 patients were discharged with drains on 2nd day. 1.42 ± 0.49 days were the mean stay in hospital. Conclusion: By means of a MW ultra grasper, the appendix was suspended and held, and the meso-appendix was successfully skeletonized and cauterized in two Ports Laparoscopic Appendectomy. To manipulate the appendix, it is helpful to insert the MW ultra grasper into the cavity of abdomen at the McBurneys point and leave no visible scarring.